2006
DOI: 10.1021/ac061417b
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Nontumor Bladder Tissue and Tumor by Raman Spectroscopy

Abstract: We have applied Raman spectroscopy to discriminate between nontumor and tumor bladder tissue and to determine the biochemical differences therein. Tissue samples from 15 patients were collected, and frozen sections were made for Raman spectroscopy and histology. Twenty-five pseudocolor Raman maps were created in which each color represents a cluster of spectra measured on tissue areas of similar biochemical composition. For each cluster, the cluster-averaged spectrum (CAS) was calculated and classified as tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 27 publications
6
99
0
2
Order By: Relevance
“…This can be a tedious process and it may not be able to extract the more complex, correlated spectral features that best separate the groups. Multivariate statistical methods [29][30][31] have been shown to be powerful approaches for analyzing multidimensional spectral data for the purposes of optimizing group separation and classifying unknown objects to groups. Principal component analysis (PCA) is a popular technique for unsupervised analysis of spectra.…”
Section: Spectral Analysismentioning
confidence: 99%
“…This can be a tedious process and it may not be able to extract the more complex, correlated spectral features that best separate the groups. Multivariate statistical methods [29][30][31] have been shown to be powerful approaches for analyzing multidimensional spectral data for the purposes of optimizing group separation and classifying unknown objects to groups. Principal component analysis (PCA) is a popular technique for unsupervised analysis of spectra.…”
Section: Spectral Analysismentioning
confidence: 99%
“…5). For example, previous studies published by Stone et al, 32 Grimbergen et al 8 and de Jong et al 10 have shown good spectra for samples recorded at 830 nm/845 nm using calcium uoride substrates, which could be achieved here by simply increasing the laser power, enlarging the confocal aperture or increasing the exposure time. The results shown here may also be accounted for by considering the signicantly lower number of scattered photons for higher laser wavelengths (see Section 2.2 on spectral resolution) and the quantum efficiency of the CCD detector used for recording spectra.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have reported the use of a wide range of substrates including calcium uoride, [8][9][10] aluminium, 11,12 quartz 13-15 and 3D collagen gels. 16 However, substrates that produce low background signals for NIR sources are oen expensive, and are available in different levels of purity/lm thicknesses, which can produce variable results with Raman spectroscopy.…”
Section: Sample Substratesmentioning
confidence: 99%
“…De Jong et al (2006) clearly outlined the prerequisites which must be met to promote RS to the state of clinical in vivo application. First, a database of spectra must be established that is representative of normal and diseased tissue which may be encountered in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a classification model must be developed, based on this spectral database and histological analysis of the tissue of which spectra were obtained. Third, the accuracy of this model must be tested, and the biochemical basis for the classification model should be investigated [6].…”
Section: Discussionmentioning
confidence: 99%